Literacy house as a means of fostering the people: strategies for increasing islamic-based reading interest - Hanifah Noviandari; Mohd Nazri bin Abdul Rahman (At Turots: Jurnal Pendidikan Islam, 2024)
The background of this research is the low interest in reading the community, which is a challenge in building an Islamic literacy culture in the village. The purpose of the study is to find out the strategies that can be implemented, as well as to identify the supporting and inhibiting factors. The research method is qualitative with a phenomenological approach. Data were collected through interviews, observations, and documentation, and analysed using Miles, Huberman, Saldana's interactive model analysis techniques and applying Henry Mintzberg's 5P Theory. The results of the study show that the Sidoharjo Village Literacy House has succeeded in increasing people's interest in reading with a 5P theory-based strategy. Careful planning is well implemented. The tactics are carried out by Islamic fairy tale competitions, and social media campaigns. A pattern of reading habits that continues to be developed consistently. The strategic position of the Literacy House as a center for non-formal literacy and perspectives that respect local values also strengthens the attractiveness of the program, increasing citizen participation and ownership. Supporting factors include needs surveys and cooperation with local publishers, selection and procurement of structured reading materials, improvement of library facilities and interactive activities, evaluation and feedback collection. In addition, the inhibiting factors include a lack of awareness and limited knowledge about the benefits of reading, limited collections, lack of literacy education, budget limitations, and inadequate information technology infrastructure. The contribution of this research is to provide a model of a strategy for increasing reading interest that can be applied in other regions, as well as to recommend collaboration between the government, the community, and educational institutions to build a strong Islamic-based reading culture in the community.